The decision criteria, the returns and the well-being of TVET as human capital investment in Malaysia / Muhammad Adidinizar Zia Ahmad Kusairee - Zia Ahmad Kusairee, Muhammad Adidinizar (2021)
Malaysia requires a large group of skilled workers to build, expand and eventually sustain its economic growth to become a high-income country. However, current TVET institutions in Malaysia are far from being able to supply Malaysia with sufficient skilled workers in the future. This may be due to negative perceptions of parents and students in choosing TVET as an educational pathway. Therefore, it is imperative to understand the criteria and priorities of parents and students in choosing an educational pathway. Moreover, it is also important to determine if TVET jobs are inferior to non-TVET jobs in term of income and work-life wellbeing. In this study, a group of 80 parents’ and 80 secondary school students’ judgements are analysed using Analytical Hierarchy Process (AHP). Subsequently, household income surveys (HIS) for the years 2007 to 2016 are used to examine the income difference between TVET graduates and non-TVET graduates using multiple regression analysis. Finally, surveys distributed to 180 TVET graduates and 180 non-TVET graduates are analysed using PLS-SEM. This study found that parents strongly influence the decision-making process of choosing an educational pathway for their children, and for parents to be inclined to enrol their children to an educational pathway, especially TVET, it must satisfy the criteria of fulfilling their children’s aptitude, children’s career prospects, children’s aspirations, courses offered by the educational institution and opportunities for their children to seek new knowledge. The findings also show that TVET jobs are no worse than non-TVET jobs in term of income (especially for middle and lower income earners) and work-life wellbeing.